(untitled) (Architecture Image Studies, 2026)
The increasing dominance of social media in the lives of children in Sinjai Regency has shaped their mindsets, behaviours, and social interactions. This situation highlights the need for social media detoxification as an effort to maintain balanced technology use. This study examines the extent to which the effectiveness of interpersonal communication between parents and children influences social media detoxification among children in Sinjai Regency. The research employs a descriptive quantitative design, involving 253 families as respondents. Data were collected using Likert-scale questionnaires and analysed using statistical procedures. The findings indicate a difference in perception regarding the effectiveness of interpersonal communication: parents rated it at 58%, while children rated it higher at 62%. Overall, the effectiveness of interpersonal communication is categorised as moderate. The level of social media detoxification among children also falls within the moderate category, with a score of 63%. Regression analysis reveals a significance value of p = 0.000 (p < 0.05) and an R² value of 0.133, confirming that interpersonal communication significantly influences children’s social media detoxification, although its contribution is relatively small. These findings underscore the need for strengthening family communication, social support, and digital literacy to promote responsible and balanced social media usage among children.